Statistical optimization oF process conditions for bioethanol production by solid state bioconversion of rice straw - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Ismail, M. Hafiz (2007)
Solid state bioconversion (SSB) of rice straw for bioethanol production by the compatible mixed culture of Saccharomyces cerevisiae, Trichoderma harzianum, and Phanerocheate chrysosporium was carried out in the laboratory. Design of the experiment and statistical analysis for optimization of bioethanol production was done using statistical software Minitab. The optimization was done using central composite design (CCD) with five factors: moisture content, pH, inoculum size, co-substrate (wheat flour), and minerals with five levels for all parameters. A regression model was developed with the experimental results obtained from CCD. The highest production of bioethanol was found to be 12.6% (v/v) on the sixth day of fermentation. The optimization study of the processing conditions enhanced the bioethanol production and thus achieved the optimum yield. From the optimization study, maximum production of ethanol is obtained at 60 % (v/v) of moisture, 7 pH, 4% inoculum size, 4% co-substrate (wheat flour), and 4% of minerals with its experimental and predicted valuse to be 12.6% (v/v) and 12.8% (v/v), respectively.